Extraction of crude oil from petrochemical sludge: Characterization of products using thermogravimetric analysis. (15th January 2017) - Hu, Jieqiong; Gan, Jinhua; Li, Jinping; Luo, Ying; Wang, Guangkun; Wu, Liang; Gong, Yimin
Highlights: Study on the optimal conditions for the extraction of crude oil. At lower distillation temperature for recovery of organic solvent could not only save heating cost, but also prevent thermo degradation. The temperatures of weight loss of crude oil extraction were analyzed by TGA curves. With the heating rate increased, the time of pyrolysis was shortened, the total weight loss rate decreased and the stage of maximum weight loss rate moved towards higher temperature. Abstract: In this study, solvent extraction was used to recover oil from petrochemical sludge. Three solvents were chosen to mix with petrochemical sludge to ensure adequate miscibility of crude oil in solvent under an appropriate condition. The petrochemical sludge, crude oil sample and residual petrochemical sludge were analyzed by thermogravimetric analysis (TGA). The experiments were performed at three different heating rates (10, 20, 30 °C/min) under nitrogen atmosphere. The aim of the study was to recover and evaluate crude oil from petrochemical sludge and assess the commercial potential of recycling the crude oil. Experimental results showed that the common temperature range of weight loss of the crude oil sample was about 200–550 °C. The residual petrochemical sludge still remained the partial characteristics of petrochemical sludge, which demonstrated that the residual petrochemical sludge still had the value of exploiting and utilizing for further research.